Palladium supported on fluorite structured redox CeZrO4-δ for heterogeneous suzuki coupling in water: a green protocol - Burange, Anand S.; Shukla, Rakesh; Tyagi, Avesh Kumar; Gopinath, Chinnakonda S. (Chemistry Select, 2016)
Pd on redox CeZrO4-δ catalysts was prepared, characterized and their activity was evaluated for Suzuki coupling reaction in water under reflux condition. Fresh and reduced form of 5 % Pd (R−Pd5) on CeZrO4-δ catalyst exhibited 100 % conversion in 2.5 and 1 h, respectively. R−Pd5 shows significant activity for wide range of substrate compatibility and for less reactive aryl bromides too. The mechanistic investigations proved the important role of redox CeZrO4-δ support on the catalytic activity. It was observed that the presence of oxygen vacancy along with Ce3+ enhances the activity. 1 wt % Pd photodeposited on pre-reduced CeZrO4-δ support requires a mere 20 min. for 100 % conversion of Suzuki coupling. Effect of metal dispersion and particle size on catalytic activity is also discussed. High Pd dispersion with small particle size (4±1 nm), particle size preservation after reaction, strong metal-support interaction and no leaching fully suggest the heterogeneous mechanism is operative for Suzuki coupling on 1 wt % Pd photodeposited on reduced CeZrO4-δ support. Present work hints the possibility of achieving high conversion for Suzuki reaction with very small amount of Pd through better dispersion by taking advantage of redox support and in water.